PENGARUH KONFLIK PERAN GANDA, LINGKUNGAN KERJA, DAN STRES KERJA TERHADAP KINERJA TENAGA MEDIS DAN PARAMEDIS WANITA PADA PUSKESMAS RENDANG KARANGASEM - Ni Komang Ayu Ananda Putri; I Wayan Sujana; Ni Nyoman Ari Novarini (VALUES, 2021)
Multiple roles conflict is a conflict that arises from pressures from work and family and is a potential source of work stress. One of the pressures from work arises from the non-physical work environment. Relationships around the workplace, both relationships with superiors, subordinates, and relationships with colleagues that cannot be ignored. Research in this case wanted to know the effect of multiple role conflicts, work environment, and work stress on the performance of female medical personnel and paramedics. The population in this study were all married female medical and paramedical personnel at the Rendang Karangasem Health Center, totaling 47 people. The sample size was determined using the simple random sampling technique where all members of the population were sampled, namely as many as 47 married women medical and paramedical personnel. The results of this study indicate that Multiple Role Conflict, Work Environment, and Work Stress have a negative and significant effect on the decline in the performance of female medical personnel and paramedics. Further research can develop this research by using other variables which theoretically have an influence on the performance of female medical personnel and paramedics.